2020
DOI: 10.4097/kja.19332
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided percutaneous intercostal cryoanalgesia for multiple weeks of analgesia following mastectomy: a case series

Abstract: Background: Acute post-mastectomy pain is frequently challenging to adequately treat with local anesthetic-based regional anesthesia techniques due to its relatively long duration measured in multiple weeks. Case: We report three cases in which preoperative ultrasound-guided percutaneous intercostal nerve cryoneurolysis was performed to treat pain following mastectomy. Across all postoperative days and all three patients, the mean pain score on the numeric rating scale was 0 for each day. Similarly, no patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
0
17
0
1
Order By: Relevance
“…37 38 In its percutaneous modality, the most recent review reports three cases of mastectomy with very good results. 39 This is why we encourage the search for or broadening of the field of use of PCr in other pediatric surgical procedures associated with marked postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…37 38 In its percutaneous modality, the most recent review reports three cases of mastectomy with very good results. 39 This is why we encourage the search for or broadening of the field of use of PCr in other pediatric surgical procedures associated with marked postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 Three patients who received cryoneurolysis of the second to fifth intercostal nerves before uni-or bilateral mastectomy reported a near-painless postoperative course without any opioid requirements or sleep disturbances, a significant improvement over historic controls. 54 Ultrasound-guided percutaneous cryoneurolysis may also be used in the extremities, such as to provide analgesia *This retrospective study reported a dramatic difference between the treatment (cryoneurolysis) and control groups, but due to a very small sample size (n = 6), statistics were not applied to the data. after limb or digit amputation of either the upper or lower extremity.…”
Section: Percutaneous Application To Acute Painmentioning
confidence: 99%
“…In general, even probes with trocar tips require a sharper introducer such as an intravenous angiocatheter to enable passage through the skin and muscle to the target nerve; so, it is unclear how beneficial hemispherical/blunt tips are in practice. [54][55][56]92 Ice balls are easiest to visualize with high-frequency linear transducers, but power Doppler may improve imaging with low-frequency linear-array transducers used for deeper structures. 109 Because of the hyperechoic border of the ice ball resulting from the higher acoustic impedance at the border between frozen and unfrozen tissues, [110][111][112] acoustic shadowing can limit visualization when the nerve is deeper than the ice ball.…”
Section: Equipmentmentioning
confidence: 99%
“…Last year, most journals mass produced COVID-19 related literature, and the citation of such studies has also increased. The next two most cited studies were two reports of ultrasound-guided regional blocks [ 4 , 5 ]. The surge in the interest in multimodal analgesia is thought to have had a synergistic effect on interest in the literature on various regional blocks.…”
Section: Bibliometric Analysismentioning
confidence: 99%